Industrial districts evolving in glocal value chains: evidence from the Italian wine industry - De Marchi, Valentina; Grandinetti, Roberto (Piccola Impresa / Small Business, 2016)
Drawing from recent empirical literature on Italian industrial districts, this paper sketches an outline for interpreting the changes that have recently been taking place, in the face of strong competition on a global scale in light of the global value chain perspective. Departing from an analysis of the reasons why Italian districts have lost the Marshallian characteristics, we seek to explain why we see some districts well on the road to decline, while others have succeeded in evolving and reproducing the district form. The cornerstone of our analysis focuses on the district firms that can boast an international entrepreneurship, and on the relationship they fuel within districts. A look at some of the Italian winemaking districts adds to our considerations, confirming the utility of taking a global value analysis perspective in order to see where Italian industrial districts are heading.